Production process of super-high-strength 7-series aluminum alloy for automobile bumper beam

CN122811560APending Publication Date: 2026-09-25广东豪美技术创新研究院有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611025650.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

然而,该方案引入快冷处理、预变形和回归再时效等多道附加工序,工艺路线复杂、成本较高,且其最终应用领域为通用结构材料,未针对汽车防撞梁在三点弯曲条件下的抗裂纹开裂性能进行专门优化

Benefits of technology

1.本发明通过优化合金成分,并采用三级均匀化处理以及双级时效处理,协同作用,通过有效释放内应力,分级回溶粗大相,减轻偏析,Al3Zr粒子均匀析出,钉扎晶界、细化组织,减少共晶相的方式,使得制备得到的7系铝合金屈服强度达到560MPa以上,相比于现有技术有显著的提升,满足高端汽车防撞梁对超高强度的使用要求,且应用于汽车防撞梁后,其高屈服强度与优异的抗裂纹扩展能力,使得防撞梁在碰撞过程中能够有效吸收能量且不发生纵向撕裂,显著提升了车辆的被动安全性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122811560A_ABST
    Figure CN122811560A_ABST
Patent Text Reader

Abstract

The application discloses a production process of an ultrahigh-strength 7-series aluminum alloy for an automobile anti-collision beam and belongs to the technical field of aluminum alloy preparation. The alloy component is optimized, and three-stage homogenization and two-stage aging are adopted for cooperative treatment. The three-stage homogenization releases the stress in the ingot, releases coarse phases in stages, promotes the dispersion precipitation of Al3Zr to pin the grain boundary, and refines the structure through low-temperature pretreatment. The two-stage aging makes a large number of fine η' phases precipitate in the grains and the grain boundary precipitated phases discontinuously distribute in the form of spheres, so that the yield strength reaches more than 560 MPa, and the fracture toughness is significantly improved. The product is verified through quasi-static three-point bending, and no transverse and longitudinal cracks and no tearing after crushing are found. In addition, multiple refining and a composite refining agent of potassium fluoroaluminate / potassium chloride / calcium carbonate are adopted for refining treatment, so that hydrogen and slag are effectively removed, and the performance consistency is ensured. The application overcomes the technical problems that the strength of high-strength aluminum alloy is improved, the toughness is reduced, and the product is prone to cracking, and meets the strict requirements of the automobile anti-collision beam on ultrahigh strength and collision safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy production technology, and more specifically, to a production process for ultra-high strength 7-series aluminum alloys used in automotive anti-collision beams. Background Technology

[0002] The continuous improvement in automotive lightweighting and passive safety performance has made 7-series Al-Zn-Mg-Cu aluminum alloys the mainstream material for automotive crash beams due to their high specific strength. Currently, the industry's conventional production process generally employs a two-stage homogenization and single-stage aging process to prepare 7-series aluminum alloy crash beam profiles. Specific process parameters are typically: two-stage homogenization at 465~480℃ for 18~24 hours, followed by a 485~495℃ hold for 12~18 hours, and single-stage aging at 125~140℃ for 20~26 hours. This conventional process has significant limitations; the yield strength of the product is approximately 545MPa, and longitudinal cracks easily appear on the back of the indenter during quasi-static three-point bending tests, making it difficult to meet the ultra-high strength and high toughness requirements of high-end automotive crash beams.

[0003] To address the aforementioned technical problems, there has been considerable research in existing technologies. For example, Chinese patent application CN202210843298.7 discloses a 7-series aluminum alloy material for hot forming and its manufacturing method. This method utilizes a close combination of alloy composition design, a three-stage homogenization process, appropriate hot rolling pass matching, and a two-stage continuous annealing process to control the distribution of precipitated phases and the composition of the texture, resulting in a tensile yield strength exceeding 530 MPa after forming and aging treatment. However, this patent primarily targets hot-formed sheet metal. Its three-stage homogenization process and two-stage continuous annealing process have relatively long process chains, and the final yield strength only reaches approximately 530 MPa. When applied to the fabrication of load-bearing components such as crash beams, the strength remains insufficient. Furthermore, its process focuses on improving the uniform plastic forming performance rather than simultaneously enhancing strength and toughness. For example, Chinese patent application CN202311736202.8 discloses a method for improving the strength of 7xxx series aluminum alloys. This method employs a three-stage homogenization process, rapid cooling combined with pre-deformation and re-aging heat treatment to enhance strength. The first homogenization is performed at 280℃ for 1 hour, the second at 400℃ for 3 hours, and the third at 480℃ for 12 hours followed by rapid cooling at 300℃ / s. Subsequent pre-deformation and re-aging heat treatments further enhance strength. However, this method introduces multiple additional processes, including rapid cooling, pre-deformation, and re-aging, resulting in a complex process route and high cost. Furthermore, its final application is in general structural materials, and it does not specifically optimize for the crack resistance of automotive anti-collision beams under three-point bending conditions.

[0004] Therefore, the existing technology still has the following problems that urgently need to be solved: First, the conventional two-stage homogenization process lacks a low-temperature pretreatment stage, resulting in insufficient stress relief inside the ingot and incomplete removal of dendrite segregation and coarse second phases, which can easily become crack sources; Second, the single-stage aging process can easily cause continuous coarse precipitates at grain boundaries, leading to low fracture toughness of the alloy and longitudinal cracking during three-point bending; Third, some improved solutions have complex process routes (such as requiring additional processes like rapid cooling and pre-deformation), which increases the difficulty and cost of industrial application; Fourth, there are no reported technical solutions for the specific application scenario of automotive anti-collision beams that can simultaneously improve strength and toughness and completely solve the problem of three-point bending cracking without changing the extrusion parameters. Summary of the Invention

[0005] Based on this, in order to solve one of the above-mentioned technical problems, the present invention provides a manufacturing process for ultra-high strength 7-series aluminum alloy for automotive anti-collision beams, the specific technical solution of which is as follows: A manufacturing process for ultra-high strength 7-series aluminum alloy used in automotive anti-collision beams, the manufacturing process comprising the following steps: S1. Prepare aluminum alloy raw materials according to the alloying elements of ultra-high strength 7-series aluminum alloys; S2. The aluminum alloy raw material is added to the melting furnace, the heating rate of the melting furnace is controlled, and the material is melted and then electromagnetically stirred to obtain the aluminum alloy melt. S3. The aluminum alloy melt is refined, slag removed and degassed, and then cast to obtain an aluminum alloy ingot; S4. The aluminum alloy ingot is subjected to a three-stage homogenization process; S5. The aluminum alloy ingot that has undergone three-stage homogenization treatment is extruded and then quenched by online high-intensity spraying to obtain the extruded product. S6. The extruded product is subjected to a two-stage aging treatment to obtain an ultra-high strength 7-series aluminum alloy.

[0006] Further, in step S1, the alloying elements comprise the following chemical composition by mass percentage: Zn: 7.2~8.0%, Mg: 1.6~2.0%, Cu: 1.0~1.4%, Zr: 0.12~0.18%, Fe≤0.15%, Si≤0.10%, Ti≤0.03%, with the balance being Al and unavoidable impurities.

[0007] Further, in step S1, the mass ratio of Zn to Mg in the alloying elements is 3.6 to 5.0.

[0008] Further, in step S2, the heating rate is 12~15℃ / min, and the temperature is raised to 720~760℃, and the melting process is carried out for 30~60min.

[0009] Furthermore, in step S3, the refining temperature is 700~720℃, the refining process is performed no less than 3 times, each time for no less than 10~20 minutes, and the interval between each refining process is 20~30 minutes.

[0010] Further, in step S4, the three-stage homogenization process includes: first-stage homogenization: holding at 330~360℃ for 6~10h; second-stage homogenization: holding at 465~480℃ for 18~24h; and third-stage homogenization: holding at 485~495℃ for 12~18h.

[0011] Further, in step S4, the three-stage homogenization process includes: first-stage homogenization: heating to 330-360℃ at a heating rate of 50-60℃ / h and holding for 6-10h; second-stage homogenization: heating to 465-480℃ at a heating rate of 20-30℃ / h and holding for 18-24h; third-stage homogenization: heating to 485-495℃ at a heating rate of 10-15℃ / h and holding for 12-18h.

[0012] Furthermore, in step S5, during the extrusion molding process, the extrusion ratio is 10~30, the extrusion cylinder temperature is 440~470℃, the extrusion speed is 1.5~4.0 m / min, and the extrusion outlet profile temperature is ≥460℃.

[0013] Furthermore, in step S5, the cooling rate of the online high-intensity spray quenching is 10~30℃ / s, and the outlet temperature of the profile after quenching is ≤50℃.

[0014] Furthermore, in step S6, the two-stage aging process is as follows: heat treatment at 100~115℃ for 6~10h, followed by heat treatment at 125~140℃ for 14~20h.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention optimizes the alloy composition and employs a three-stage homogenization process and a two-stage aging process. Through the synergistic effect of these processes, internal stress is effectively released, coarse phases are dissolved in stages, segregation is reduced, Al3Zr particles precipitate uniformly, grain boundaries are pinned, the microstructure is refined, and eutectic phases are reduced. This results in a 7-series aluminum alloy with a yield strength exceeding 560 MPa, a significant improvement over existing technologies. This meets the ultra-high strength requirements of high-end automotive crash beams. Furthermore, when applied to automotive crash beams, its high yield strength and excellent crack propagation resistance enable the crash beams to effectively absorb energy during collisions without longitudinal tearing, significantly improving the passive safety performance of vehicles.

[0016] 2. The refining process of this invention employs multiple refining steps and controls the refining parameters, combined with a specific ratio of refining agents (potassium fluoroaluminate, potassium chloride, and calcium carbonate), to effectively remove impurities such as hydrogen and oxide inclusions from the melt, reduce internal defects in the ingot, and have a significant positive effect on subsequent homogenization and aging treatment, further ensuring the consistency and reliability of the product's mechanical properties.

[0017] 3. This invention effectively eliminates internal ingot stress, reduces dendritic segregation and coarse second phases through the low-temperature pretreatment stage in the three-stage homogenization process. Combined with the two-stage aging treatment, it spheroidizes the grain boundary precipitates and makes them discontinuously distributed, while precipitating a large number of fine η' phases within the grains. This significantly improves the fracture toughness of the alloy while increasing its strength. Quasi-static three-point bending tests verified that the product showed no transverse or longitudinal cracks and no tearing after crushing, overcoming the technical challenge of high-strength aluminum alloys where "increased strength leads to decreased toughness and easy cracking." Attached Figure Description

[0018] The invention will be further understood from the following description taken in conjunction with the accompanying drawings. The components in the drawings are not necessarily drawn to scale, but rather the emphasis is on illustrating the principles of the embodiments. In different views, the same reference numerals designate corresponding parts.

[0019] Figure 1 Macroscopic photograph of the three-point bending test of the ultra-high strength 7-series aluminum alloy prepared in Example 1 of this invention; Figure 2 This is a macroscopic photograph of the 7-series aluminum alloy prepared in Comparative Example 1 of this invention, taken during a three-point bending test. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to its embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and do not limit the scope of protection of the invention.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0022] A manufacturing process for ultra-high strength 7-series aluminum alloy used in automotive anti-collision beams according to one embodiment of the present invention includes the following steps: S1. Prepare aluminum alloy raw materials according to the alloying elements of ultra-high strength 7-series aluminum alloys; S2. The aluminum alloy raw material is added to the melting furnace, the heating rate of the melting furnace is controlled, and the material is melted and then electromagnetically stirred to obtain the aluminum alloy melt. S3. The aluminum alloy melt is refined, slag removed and degassed, and then cast to obtain an aluminum alloy ingot; S4. The aluminum alloy ingot is subjected to a three-stage homogenization process; S5. The aluminum alloy ingot that has undergone three-stage homogenization treatment is extruded and then quenched by online high-intensity spraying to obtain the extruded product. S6. The extruded product is subjected to a two-stage aging treatment to obtain an ultra-high strength 7-series aluminum alloy.

[0023] In one embodiment, in step S1, the alloying elements comprise the following chemical composition by mass percentage: Zn: 7.2~8.0%, Mg: 1.6~2.0%, Cu: 1.0~1.4%, Zr: 0.12~0.18%, Fe≤0.15%, Si≤0.10%, Ti≤0.03%, with the balance being Al and unavoidable impurities.

[0024] In one embodiment, in step S1, the mass ratio of Zn to Mg in the alloying elements is 3.6 to 5.0. This invention, by limiting the mass ratio of Zn to Mg, demonstrates that the Zn / Mg ratio plays a crucial role in the aging precipitation strengthening effect of 7-series aluminum alloys. It ensures that a sufficient number of η' phases, rather than the equilibrium η phase, precipitate during the aging process, thus contributing to increased strength.

[0025] In one embodiment, in step S2, the heating rate is 12~15℃ / min, and the temperature is raised to 720~760℃ for smelting treatment for 30~60min.

[0026] In one embodiment, in step S3, the refining temperature is 700~720℃, the refining process is performed no less than 3 times, each time for no less than 10~20 minutes, and the interval between each refining process is 20~30 minutes.

[0027] In one embodiment, a refining agent is added during each refining process, and the amount of refining agent added each time is 0.1 to 0.3% of the total mass of the aluminum alloy melt.

[0028] In one embodiment, the refining agent is obtained by mixing potassium fluoroaluminate, potassium chloride, and calcium carbonate in a mass ratio of (1~7):(1~5):(1~3). This invention can gradually remove hydrogen, oxide inclusions, and floating impurities from the melt through multiple refining processes. Allowing the melt to stand for 20~30 minutes after each refining step promotes the full floating of inclusions, thereby effectively improving the purity of the molten aluminum.

[0029] In one embodiment, the casting temperature is 700~740℃ and the casting speed is 30~60mm / min.

[0030] In one embodiment, step S4 includes the following three-stage homogenization process: first-stage homogenization: holding at 330~360℃ for 6~10h; second-stage homogenization: holding at 465~480℃ for 18~24h; and third-stage homogenization: holding at 485~495℃ for 12~18h.

[0031] In one embodiment, step S4, the three-stage homogenization process includes: first-stage homogenization: heating to 330-360℃ at a heating rate of 50-60℃ / h and holding for 6-10h; second-stage homogenization: heating to 465-480℃ at a heating rate of 20-30℃ / h and holding for 18-24h; and third-stage homogenization: heating to 485-495℃ at a heating rate of 10-15℃ / h and holding for 12-18h. During the melting and casting process, rapid cooling of ingots generates significant residual thermal stress. The superposition of thermal stress and casting residual stress can lead to direct cracking of the ingot during homogenization. This invention effectively prevents thermal cracking during homogenization by using a gradient heating rate, making it particularly suitable for the industrial production of ingots for large-size anti-collision beams. If the heating rate is too fast, the internal temperature distribution of the ingot will be uneven, and some areas may exceed the melting point of the eutectic phase, causing overheating. If the heating rate is too slow, production efficiency will decrease. Furthermore, by limiting the process parameters of the three-stage homogenization process, this invention achieves multiple beneficial effects, including stress relief, gradual dissolution of the eutectic phase, dispersed precipitation of Al3Zr, and improved microstructure uniformity.

[0032] In one embodiment, in step S5, during the extrusion molding, the extrusion ratio is 10~30, the extrusion cylinder temperature is 440~470℃, the extrusion speed is 1.5~4.0 m / min, and the extrusion outlet profile temperature is ≥460℃.

[0033] In one embodiment, in step S5, the cooling rate of the online high-pressure spray quenching is 10~30℃ / s, and the outlet temperature of the profile after quenching is ≤50℃.

[0034] In one embodiment, in step S6, the two-stage aging process is as follows: heat treatment at 100~115℃ for 6~10h, followed by heat treatment at 125~140℃ for 14~20h.

[0035] In one embodiment, the present invention also provides an automotive anti-collision beam, which is obtained by the production process of ultra-high strength 7-series aluminum alloy used in automotive anti-collision beams. The yield strength of the automotive anti-collision beam is ≥560MPa, and there are no transverse or longitudinal cracks in the quasi-static three-point bending test, and no tearing after crushing.

[0036] The implementation schemes of the present invention will now be described in detail with reference to specific embodiments.

[0037] Example 1: A manufacturing process for ultra-high strength 7-series aluminum alloy used in automotive anti-collision beams, the manufacturing process comprising the following steps: S1. Prepare aluminum alloy raw materials according to the alloying elements of ultra-high strength 7-series aluminum alloys: the alloying elements include the following chemical composition by mass percentage: Zn: 7.6%, Mg: 1.8%, Cu: 1.2%, Zr: 0.15%, Fe: 0.03%, Si: 0.02%, Ti: 0.02%, with the balance being Al and unavoidable impurities; S2. The aluminum alloy raw material is added to the melting furnace, the heating rate of the melting furnace is controlled at 12℃ / min, and the temperature is raised to 740℃. The melting process is carried out for 60 minutes, and after electromagnetic stirring, the aluminum alloy melt is obtained. S3. The aluminum alloy melt is refined three times at 700°C, each refining process lasting 15 minutes, with a 20-minute interval between each refining process. Each refining process requires the addition of a refining agent (0.1% of the total mass of the aluminum alloy melt, which is obtained by mixing potassium fluoroaluminate, potassium chloride, and calcium carbonate in a mass ratio of 5:3:2) to remove slag and degas the material. Then, the material is cast at 720°C at a casting speed of 50 mm / min to obtain an aluminum alloy ingot. S4. The aluminum alloy ingot is subjected to a three-stage homogenization treatment, which includes: first-stage homogenization: heating to 350°C at a heating rate of 60°C / h and holding for 8 hours; second-stage homogenization: heating to 475°C at a heating rate of 25°C / h and holding for 22 hours; third-stage homogenization: heating to 490°C at a heating rate of 10°C / h and holding for 16 hours. S5. The aluminum alloy ingot that has completed the three-stage homogenization treatment is extruded and formed with an extrusion ratio of 25, an extrusion barrel temperature of 450℃, an extrusion speed of 3.0m / min, and an extrusion outlet profile temperature of 480℃. Then, it is quenched by online strong spraying with a cooling rate of 30℃ / s. The outlet temperature of the quenched profile is 30℃, and the extruded product is obtained. S6. The extruded product is subjected to a two-stage aging treatment, wherein the two-stage aging treatment process is as follows: heat treatment at 110℃ for 8 hours, followed by heat treatment at 135℃ for 18 hours, to obtain an ultra-high strength 7-series aluminum alloy.

[0038] Example 2: A manufacturing process for ultra-high strength 7-series aluminum alloy used in automotive anti-collision beams, the manufacturing process comprising the following steps: S1. Prepare aluminum alloy raw materials according to the alloying elements of ultra-high strength 7 series aluminum alloys: the alloying elements include the following chemical composition by mass percentage: Zn: 7.4%, Mg: 1.6%, Cu: 1.4%, Zr: 0.16%, Fe: 0.03%, Si: 0.03%, Ti: 0.02%, with the balance being Al and unavoidable impurities; S2. The aluminum alloy raw material is added to the melting furnace, the heating rate of the melting furnace is controlled at 12℃ / min, and the temperature is raised to 740℃. The melting process is carried out for 60 minutes, and after electromagnetic stirring, the aluminum alloy melt is obtained. S3. The aluminum alloy melt is refined three times at 700°C, each refining process lasting 15 minutes, with a 20-minute interval between each refining process. Each refining process requires the addition of a refining agent (0.1% of the total mass of the aluminum alloy melt, which is obtained by mixing potassium fluoroaluminate, potassium chloride, and calcium carbonate in a mass ratio of 5:3:2) to remove slag and degas the material. Then, the material is cast at 720°C at a casting speed of 50 mm / min to obtain an aluminum alloy ingot. S4. The aluminum alloy ingot is subjected to a three-stage homogenization treatment, which includes: first-stage homogenization: heating to 340°C at a heating rate of 50°C / h and holding for 10h; second-stage homogenization: heating to 465°C at a heating rate of 20°C / h and holding for 24h; third-stage homogenization: heating to 485°C at a heating rate of 10°C / h and holding for 18h. S5. The aluminum alloy ingot that has completed the three-stage homogenization treatment is extruded and formed with an extrusion ratio of 25, an extrusion barrel temperature of 450℃, an extrusion speed of 3.0 m / min, and an extrusion outlet profile temperature of 480℃. Then, it is quenched by online strong spraying with a cooling rate of 30℃ / s. The outlet temperature of the quenched profile is 30℃, and the extruded product is obtained. S6. The extruded product is subjected to a two-stage aging treatment, wherein the two-stage aging treatment process is as follows: heat treatment at 115°C for 7 hours, followed by heat treatment at 130°C for 16 hours, to obtain an ultra-high strength 7-series aluminum alloy.

[0039] Example 3: A manufacturing process for ultra-high strength 7-series aluminum alloy used in automotive anti-collision beams, the manufacturing process comprising the following steps: S1. Prepare aluminum alloy raw materials according to the alloying elements of ultra-high strength 7-series aluminum alloys: the alloying elements include the following chemical composition by mass percentage: Zn: 7.5%, Mg: 1.7%, Cu: 1.3%, Zr: 0.18%, Fe: 0.02%, Si: 0.03%, Ti: 0.02%, with the balance being Al and unavoidable impurities; S2. The aluminum alloy raw material is added to the melting furnace, the heating rate of the melting furnace is controlled at 12℃ / min, and the temperature is raised to 740℃. The melting process is carried out for 60 minutes, and after electromagnetic stirring, the aluminum alloy melt is obtained. S3. The aluminum alloy melt is refined three times at 700°C, each refining process lasting 15 minutes, with a 20-minute interval between each refining process. Each refining process requires the addition of a refining agent (0.1% of the total mass of the aluminum alloy melt, which is obtained by mixing potassium fluoroaluminate, potassium chloride, and calcium carbonate in a mass ratio of 5:2:3) to remove slag and degas the material. Then, the material is cast at 720°C at a casting speed of 50 mm / min to obtain an aluminum alloy ingot. S4. The aluminum alloy ingot is subjected to a three-stage homogenization process, which includes: first-stage homogenization: heating to 360°C at a heating rate of 60°C / h and holding for 6 hours; second-stage homogenization: heating to 470°C at a heating rate of 20°C / h and holding for 20 hours; third-stage homogenization: heating to 490°C at a heating rate of 10°C / h and holding for 15 hours. S5. The aluminum alloy ingot that has completed the three-stage homogenization treatment is extruded and formed with an extrusion ratio of 25, an extrusion barrel temperature of 450℃, an extrusion speed of 3.0m / min, and an extrusion outlet profile temperature of 480℃. Then, it is quenched by online strong spraying with a cooling rate of 30℃ / s. The outlet temperature of the quenched profile is 30℃, and the extruded product is obtained. S6. The extruded product is subjected to a two-stage aging treatment, wherein the two-stage aging treatment process is as follows: heat treatment at 110°C for 8 hours, followed by heat treatment at 135°C for 16 hours, to obtain an ultra-high strength 7-series aluminum alloy.

[0040] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that the chemical composition ratio of the alloying elements in Comparative Example 1 is different, while the rest is the same as in Example 1. The alloying elements in Comparative Example 1 comprise the following chemical composition by mass percentage: Zn: 5.3%, Mg: 2.4%, Cu: 2.2%, Zr: 0.18%, Fe: 0.02%, Si: 0.03%, Ti: 0.03%, with the balance being Al and unavoidable impurities.

[0041] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses a conventional two-stage uniform processing process and a conventional single-stage aging process, while the rest is the same as Example 1. The two-stage homogenization process in Comparative Example 2 is: heat treatment at 470℃ for 20 hours and heat treatment at 490℃ for 15 hours; the single-stage aging process is: heat treatment at 130℃ for 24 hours.

[0042] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses a conventional two-stage uniform treatment process and a conventional single-stage aging treatment process, while the rest is the same as Example 1. The two-stage homogenization process in Comparative Example 3 is: heat treatment at 465℃ for 22 hours and heat treatment at 485℃ for 16 hours; the single-stage aging process is: heat treatment at 15℃ for 22 hours.

[0043] Comparative Example 4: The difference between Comparative Example 4 and Example 1 is that the three-stage homogenization process parameters used in Comparative Example 4 are different, while the rest are the same as in Example 1. The three-stage homogenization process in Comparative Example 4 is as follows: First-stage homogenization: heating to 400℃ at a heating rate of 30℃ / h and holding for 12h; Second-stage homogenization: heating to 450℃ at a heating rate of 30℃ / h and holding for 10h; Third-stage homogenization: heating to 460℃ at a heating rate of 5℃ / h and holding for 6h.

[0044] Comparative Example 5: The difference between Comparative Example 5 and Example 1 is that Comparative Example 5 did not undergo three-stage homogenization treatment, but otherwise it was the same as Example 1.

[0045] Comparative Example 6: The difference between Comparative Example 6 and Example 1 is that the refining process in Comparative Example 6 is different, while the rest is the same as in Example 1. The refining process in Comparative Example 6 is as follows: 0.3% of the total mass of the aluminum alloy melt is added to the aluminum alloy melt as a refining agent (the refining agent is obtained by mixing potassium fluoroaluminate, potassium chloride and calcium carbonate in a mass ratio of 5:2:3), and the refining process is carried out at 700°C for 30 minutes.

[0046] Comparative Example 7: The difference between Comparative Example 7 and Example 1 is that the refining agent in Comparative Example 7 is potassium chloride alone, while the rest is the same as in Example 1.

[0047] The aluminum alloy samples prepared in Examples 1-3 and the aluminum alloy samples prepared in Comparative Examples 1-7 were subjected to performance tests, and the results are shown in Table 1 below.

[0048] Table 1: Performance Test Results

[0049] It can be seen from the data analysis in Table 1 that all Examples 1 to 3 of the present invention adopt the alloy composition defined by the present invention, three-stage homogenization (including gradient heating rate), two-stage aging and optimized refining process, and have excellent overall mechanical properties. Moreover, no transverse or longitudinal cracks are observed in the quasi-static three-point bending test, no tearing occurs after crushing, all products are judged as qualified, and meet the stringent requirements of ultra-high strength and high toughness for automobile anti-collision beams. Compared with Example 1, the alloy composition in Comparative Example 1 deviates from the scope of the present application, and the Zn / Mg ratio is about 2.2. This indicates that when the Zn / Mg ratio is too low, a sufficient amount of η' strengthening phases cannot be precipitated during the aging process, and the grain boundary precipitated phases are coarse and continuous, resulting in a significant decrease in both strength and toughness. In Comparative Examples 2 and 3, conventional two-stage homogenization and single-stage aging processes in the industry are adopted, and their mechanical properties are inferior to those of Example 1, and longitudinal cracks appear in all three-point bending tests, indicating that the conventional process has an obvious contradiction between strength and toughness, and cannot meet the application requirements of anti-collision beams. In Comparative Example 4, the process parameters of three-stage homogenization are changed, and the performance is inferior to that of Example 1. This shows that even if the three-stage homogenization process is adopted, if the parameters such as temperature, time and heating rate are not within the optimized scope of the present invention, sufficient re-dissolution and diffuse precipitation of Al3Zr still cannot be achieved, the synergistic effect with the alloy composition cannot be formed, the microstructure uniformity is poor, and the performance fails to meet the standard. In Comparative Example 5, no three-stage homogenization treatment is performed, resulting in significantly worse performance than Example 1. This shows that the unhomogenized ingot has serious dendritic segregation and coarse second phases, the microstructure is uneven after extrusion, and the aging strengthening effect is extremely poor. In Comparative Example 6, a single refining treatment process is adopted, resulting in inferior performance to Example 1. This shows that single refining cannot fully remove hydrogen and slag inclusions in the melt, and there are micro-defects inside the ingot. Although it has little influence on strength, it is easy to induce microcracks under the three-point bending stress state, which affects the product qualification rate. In Comparative Example 7, the refining agent is single potassium chloride, resulting in inferior performance to Example 1. This shows that the refining effect of single potassium chloride is limited, and oxide inclusions cannot be effectively removed, resulting in insufficient purity of the ingot, decreased microstructure uniformity, and further affecting the strength-toughness matching.

[0050] In addition, Figure 1 is a macroscopic photograph of the three-point bending test of the ultra-high-strength 7-series aluminum alloy prepared in Example 1 of the present invention, from Figure 1 it can be seen that the ultra-high-strength 7-series aluminum alloy prepared in Example 1 of the present invention has no transverse cracks and no longitudinal cracks, and the sample is qualified. The test results of the samples of Examples 2 and 3 are the same or similar to those of Example 1, and will not be repeated here; Figure 2 is a macroscopic photograph of the three-point bending test of the 7-series aluminum alloy prepared in Comparative Example 1 of the present invention, from Figure 2 it can be seen that in Comparative Example 2, obvious longitudinal cracks appear on the back of the indenter, and the sample is unqualified. The test results of Comparative Examples 3 to 7 are as described in Table 1, and will not be repeated here.

[0051] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0052] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A manufacturing process for ultra-high strength 7-series aluminum alloy used in automotive anti-collision beams, characterized in that, The production process includes the following steps: S1. Prepare aluminum alloy raw materials according to the alloying elements of ultra-high strength 7-series aluminum alloys; S2. The aluminum alloy raw material is added to the melting furnace, the heating rate of the melting furnace is controlled, and the material is melted and then electromagnetically stirred to obtain the aluminum alloy melt. S3. The aluminum alloy melt is refined, slag removed and degassed, and then cast to obtain an aluminum alloy ingot; S4. The aluminum alloy ingot is subjected to a three-stage homogenization process; S5. The aluminum alloy ingot that has undergone three-stage homogenization treatment is extruded and then quenched by online high-intensity spraying to obtain the extruded product. S6. The extruded product is subjected to a two-stage aging treatment to obtain an ultra-high strength 7-series aluminum alloy.

2. The production process according to claim 1, characterized in that, In step S1, the alloying elements comprise the following chemical composition by mass percentage: Zn: 7.2~8.0%, Mg: 1.6~2.0%, Cu: 1.0~1.4%, Zr: 0.12~0.18%, Fe≤0.15%, Si≤0.10%, Ti≤0.03%, with the balance being Al and unavoidable impurities.

3. The production process according to claim 2, characterized in that, In step S1, the mass ratio of Zn to Mg in the alloying elements is 3.6 to 5.

0.

4. The production process according to claim 1, characterized in that, In step S2, the heating rate is 12~15℃ / min, and the temperature is raised to 720~760℃ for smelting treatment for 30~60min.

5. The production process according to claim 1, characterized in that, In step S3, the refining temperature is 700~720℃, the refining process is carried out at least 3 times, each time for at least 10~20 minutes, and the interval between each refining process is 20~30 minutes.

6. The production process according to claim 1, characterized in that, In step S4, the three-stage homogenization process includes: first-stage homogenization: holding at 330~360℃ for 6~10h; second-stage homogenization: holding at 465~480℃ for 18~24h; and third-stage homogenization: holding at 485~495℃ for 12~18h.

7. The production process according to claim 6, characterized in that, In step S4, the three-stage homogenization process includes: first-stage homogenization: heating to 330-360℃ at a heating rate of 50-60℃ / h and holding for 6-10h; second-stage homogenization: heating to 465-480℃ at a heating rate of 20-30℃ / h and holding for 18-24h; and third-stage homogenization: heating to 485-495℃ at a heating rate of 10-15℃ / h and holding for 12-18h.

8. The production process according to claim 1, characterized in that, In step S5, during the extrusion molding process, the extrusion ratio is 10~30, the extrusion cylinder temperature is 440~470℃, the extrusion speed is 1.5~4.0 m / min, and the extrusion outlet profile temperature is ≥460℃.

9. The production process according to claim 1, characterized in that, In step S5, the cooling rate of the online high-intensity spray quenching is 10~30℃ / s, and the outlet temperature of the profile after quenching is ≤50℃.

10. The production process according to claim 1, characterized in that, In step S6, the two-stage aging process is as follows: heat treatment at 100~115℃ for 6~10h, followed by heat treatment at 125~140℃ for 14~20h.

Citation Information

Patent Citations

  • 7-series aluminum alloy material for hot forming and manufacturing method of 7-series aluminum alloy material

    CN115261688A

  • A preparation method for improving the strength performance of 7xxx series aluminum alloy

    CN117702017B